2010
DOI: 10.1007/s10354-010-0790-5
|View full text |Cite
|
Sign up to set email alerts
|

Dichtigkeit von Wurzelkanalfüllungen mit GuttaFlow® und Resilon™ im Vergleich zur lateralen Kondensation

Abstract: Epiphany/Resilon and GuttaFlow are newly developed methods for obturation of the root canal system. Epiphany/Resilon is a thermoplastic, synthetic polymer-based root canal filling material which enables the bonding to the dentin root canal wall during root canal obturation. GuttaFlow is a cold flowable filling system for the obturation of root canals, combining sealer and gutta-percha in one product. The purpose of this study was to assess the leakage of the Epiphany/Resilon or GuttaFlow root canal filling com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…The competitive advantage of this material was supposed to be a monoblock with dentin [179][180][181], which unfortunately did not turn out to be true [182]. There has been dispute as to whether this material is more useful, as it has been recognized in some studies [168,178,184,194,211,215,216,230,[232][233][234][235][236][237][238][239][240][241][242][243][244][245], or whether gutta-percha provides the best filling and tightness in the root canal [160,[194][195][196][197][198][199][200][201][202][203][204][205][206][207], especially after a longer time [208,209]. Many other evaluations and research results showed, and many dentists still believe, that Resilon cannot compete with gutta-percha.…”
Section: Summary and Final Commentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The competitive advantage of this material was supposed to be a monoblock with dentin [179][180][181], which unfortunately did not turn out to be true [182]. There has been dispute as to whether this material is more useful, as it has been recognized in some studies [168,178,184,194,211,215,216,230,[232][233][234][235][236][237][238][239][240][241][242][243][244][245], or whether gutta-percha provides the best filling and tightness in the root canal [160,[194][195][196][197][198][199][200][201][202][203][204][205][206][207], especially after a longer time [208,209]. Many other evaluations and research results showed, and many dentists still believe, that Resilon cannot compete with gutta-percha.…”
Section: Summary and Final Commentsmentioning
confidence: 99%
“…But opinions on this subject are not uniform, and in [182], it was even stated that this monoblock concept is not true. Statements have been presented in the literature that it is a material that legitimately competes with gutta-percha and even surpasses it; e.g., it has better adhesion to the surface of the prepared root canal [183,184]. Simultaneously, in the presence of chloroform, a distinct advantage is held by gutta-percha [185], and the opposite in the case of hydration or dampness of the root canal [186].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the long-term success of conservative endodontic treatment depends not only on the efficiency of cleaning, but also on the reliability of root canal lumen obturation. Hermetic obturation of the canal is a basic guarantee for termination of periodontal tissue antigen stimulation, creation of favorable conditions for reparative processes in periapical areas and prophylaxis of re-infection of periodontium in remote periods after completion of treatment [1][2][3][4][5][6][7][8][9]. Many methods and techniques for obturation of root canals, each with their own advantages and limitations, were suggested [10].…”
Section: Introductionmentioning
confidence: 99%
“…55 Less dye penetration has been reported with Resilon/Epiphany compared to gutta-percha/AH-plus. 56-61 Another study has shown that both materials provide the same coronal seal whereas Resilon provides the best apical seal. 62 In contrast, another investigation has shown that the coronal sealing ability is the best for Resilon.…”
Section: Introductionmentioning
confidence: 99%